2020
DOI: 10.3390/insects11110749
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Trap Color on Captures of Bark- and Wood-Boring Beetles (Coleoptera; Buprestidae and Scolytinae) and Associated Predators

Abstract: Traps baited with attractive lures are increasingly used at entry-points and surrounding natural areas to intercept exotic wood-boring beetles accidentally introduced via international trade. Several trapping variables can affect the efficacy of this activity, including trap color. In this study, we tested whether species richness and abundance of jewel beetles (Buprestidae), bark and ambrosia beetles (Scolytinae), and their common predators (i.e., checkered beetles, Cleridae) can be modified using trap colors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
19
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 80 publications
4
19
1
Order By: Relevance
“…As a non-flower visitor, P. detritus may use an achromatic visual channel, which could explain its attraction to a dark color such as purple. According to Rassati et al [9], Clerus mutillarius was caught significantly more in red and brown traps than in black traps, but black traps caught more individuals than yellow, green, and grey traps [46]. In our second field test during the present study, we saw no evidence that any of our study species were attracted to unbaited light green traps, which had previously been shown to attract P. floralis [19], a known flower feeder.…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…As a non-flower visitor, P. detritus may use an achromatic visual channel, which could explain its attraction to a dark color such as purple. According to Rassati et al [9], Clerus mutillarius was caught significantly more in red and brown traps than in black traps, but black traps caught more individuals than yellow, green, and grey traps [46]. In our second field test during the present study, we saw no evidence that any of our study species were attracted to unbaited light green traps, which had previously been shown to attract P. floralis [19], a known flower feeder.…”
Section: Discussioncontrasting
confidence: 49%
“…Adults of the predatory clerid beetle C. mutillarius are common on the ground and bark of old deciduous trees in mostly oak and beech forests [43,44] in Central and Southern Europe, and North Africa [45,46]. Clerus mutillarius is considered a bark beetle predator [47], but no experimental data is available in the literature on its range of prey.…”
Section: Discussionmentioning
confidence: 99%
“…However, other Lindgren trap colors (e.g., green, purple) also have been used to trap other woodboring insects like emerald ash borer (Agrilus planipennis Fairmaire), and these alternative colors also will generally collect Xylosandrus spp. as long as the trap is baited with an ethanol lure (Francese et al 2013;Cavaletto et al 2020;Marchioro et al 2020). Indeed, most ethanol-baited traps have been shown suitable for monitoring the presence or absence of ambrosia beetle.…”
Section: Trapsmentioning
confidence: 99%
“…This general preference of Xylosandrus spp. for dark colors over light colors, especially yellow, was confirmed also using colored-panel traps (Cavaletto et al 2020). Cross-vane sliding and sticky-coated traps (Cross-trap®, Econex, Spain) have been developed by improving the classical traps used for mass trapping of Monochamus galloprovincialis (Olivier), the vector of pine wilt nematode (Bursaphelenchus xylophilus (Steiner & Buhrer) Nickle) (Álvarez et al 2015).…”
Section: Trapsmentioning
confidence: 99%
“…To mitigate the impact of bark and wood-boring insects, improved and novel approaches are constantly sought and investigated. For example, a series of recent studies has shown that trap color largely affects the beetle species trapped [ 6 ]. Brightly colored traps (yellow, green, and blue) attract a significantly higher number of flower-visiting longhorn beetles [ 7 ] than black ones.…”
mentioning
confidence: 99%